1978
DOI: 10.1136/sti.54.3.165
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cefuroxime for the treatment of acute gonorrhoea in men.

Abstract: SUMMARY This is a report on a clinical trial in which cefuroxime was used for treating 110 men with uncomplicated urethral gonorrhoea. Twenty-three men were given 1 g cefuroxime intramuscularly and 1 g probenecid orally, and 87 were treated with 1-5 g cefuroxime intramuscularly with 1 g probenecid orally. All 18 patients treated with 1 g cefuroxime and 1 g probenecid and seen at least once after treatment, were cured. Sixty-six (98 5 %) of 67 patients treated with 15 g cefuroxime and 1 g probenecid and seen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

1979
1979
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…This regimen had produced only a 2% failure rate in a previous study (Sanchez et al 1983). Intramuscular cefuroxime 1.5g in combination with oral probenecid 19 produced failure rates of 1.5% (Price & Gluker 1978), 2.8% (Morrison et al 1980) and 4.0% (Lossick et al 1982). Similar rates were seen with 750mg and 19 doses of cefuroxime (Fowler et al 1978;Morrison et al 1980;Price & Gluker 1978).…”
Section: Gonorrhoeasupporting
confidence: 78%
See 1 more Smart Citation
“…This regimen had produced only a 2% failure rate in a previous study (Sanchez et al 1983). Intramuscular cefuroxime 1.5g in combination with oral probenecid 19 produced failure rates of 1.5% (Price & Gluker 1978), 2.8% (Morrison et al 1980) and 4.0% (Lossick et al 1982). Similar rates were seen with 750mg and 19 doses of cefuroxime (Fowler et al 1978;Morrison et al 1980;Price & Gluker 1978).…”
Section: Gonorrhoeasupporting
confidence: 78%
“…Intramuscular cefuroxime 1.5g in combination with oral probenecid 19 produced failure rates of 1.5% (Price & Gluker 1978), 2.8% (Morrison et al 1980) and 4.0% (Lossick et al 1982). Similar rates were seen with 750mg and 19 doses of cefuroxime (Fowler et al 1978;Morrison et al 1980;Price & Gluker 1978). The site of infection did not appear to influence the failure rate (Lossick et al 1982), although pharyngeal gonorrhoea was associated with a very high failure rate (46%) in I ,.report (Graudal et al 1985).…”
Section: Gonorrhoeasupporting
confidence: 74%
“…Although a number of new P-lactam antibiotics have been reported to show promising in vitro and in vivo activities (2,3,6,8,9), few can be administered orally. Of these drugs, cefaclor and amoxicillin-clavulanic acid (Augmentin) have been reported to be active against PPNG strains both in vitro and in vivo (4,10).…”
mentioning
confidence: 99%
“…There is good clinical trial evidence for the efficacy of ceftriaxone 250 mg intramuscular and cefixime 400 mg oral in gonorrhoea, and to show that these regimens are equivalent in efficacy. 17 There are also small, rather old, trials to support the use of cefuroxime 1.5 g intramuscular 18 and cefuroxime axetil 1 g oral. 19 We cannot, however, find formal validation of cefuroxime axetil at 200 mg in gonorrhoea, and one study found cefuroxime 1.0 g oral inferior to ciprofloxacin for gonococcal urethritis in men, though not for cervical infection in women.…”
Section: Discussionmentioning
confidence: 99%